The Impact of Thermal Treatment on Structural Changes of Teak and Iroko Wood Lignins - Danica Kačíková; Ivan Kubovský; Nikoleta Ulbriková; František Kačík (Applied Sciences, 2020)
Thermal modification is an environmentally friendly method to improve dimensional stability, durability, and aesthetic properties of wood. Changes in lignin as one of the main wood components markedly influence wood product properties and recycling possibilities of thermowood at the end of its life cycle. Teak and iroko wood samples were thermally treated at the temperatures of 160 °C, 180 °C and 210 °C following the Thermowood process. Dioxane lignin was isolated from treated and untreated wood and analysed by nitrobenzene oxidation (NBO), size exclusion chromatography (SEC) and Fourier transform infrared spectroscopy (FTIR). The yields of both acid-insoluble and dioxane lignins increased with an increasing treatment temperature. Dioxane lignins are GS-types containing more guaiacyl units compared to syringyl ones with S/G ratios of 0.91 and 0.84, respectively. In the process of thermal modification, several degradation and condensation reactions were observed. The cleavage of methoxyl groups and side chains, oxidation reactions, cleavage of the β-O-4 ether linkage and cross-linking radicals arising at higher temperatures were all confirmed. However, during the thermal treatment, teak lignin changed in a different way than iroko lignin, e.g., the molecular weight of iroko lignin decreased at all applied temperatures while it increased at 180 °C and 210 °C in teak lignin, and the change in S/G ratio and the cleavage of alkyl-aryl bonds are different in both wood species.